Penyuluhan Kepada Masyarakat (PKM) yang Bertujuan untuk Menekan Angka Pertumbuhan dan Penyebaran Filariasis dalam Upaya Pencegahan Penyakit Filariasis di Asrama STIkes Faathir Husada (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
Filariasis is chronic and if not treated properly can lead to permanent disability. In this case, themain vectors of Wuchereria bacrofti are Culex, Anopheles and Aedes mosquitoes. Symptoms that can arisefrom filariasis are more pronounced in men, due to heavier physical labor. In Southeast Asia, Indonesia isone of the 11 countries endemic for filariasis. Filariasis in Indonesia was first reported by Haga and Van Eecke in 1889 in Jakarta with the discovery of scrotal filariasis. Reported clinical cases tend to increasefrom year to year due to the large number of cases found along with districts / cities that carry out targetdata collection before the provision of mass preventive drugs (POPM) filariasis from 2014-2022 cumulativecases of chronic filariasis with the highest disability in East Nusa Tenggara. Indonsia can break the chainof filariasis spread by Breaking the chain of filariasis by mass drug administration in endemic areas oncea year for 5 consecutive years and Preventing and limiting disability by self-management of filariasis cases.The parasite is spread using mosquito vectors as intermediate hosts and humans or monkeys and dogs asfinal hosts. When the mosquito sucks the blood of a human/animal where the sheath detaches and thenpenetrates the abdominal wall Mosquitoes carrying microfilariae migrate into the mosquito's abdomen andin the muscle or fatty tissue in the chest area. Filariasis prevention is done by avoiding infective mosquitobites and eradicating risks associated with Filariasis incidence such as those from the environment andchanges in community behavior as well as maintaining and developing local wisdom. Identifying vectorsby detecting the presence of infective larvae in mosquitoes using human bait. For treatment, the drug usedis DEC (diethylcarbamazine citrate) is the main drug in both treatments crowds or individuals. DEC killsmicrofilariae and for adult worms.
Keywords: Prevention; Knowledge; Filariasis